2003
DOI: 10.1002/polb.10418
|View full text |Cite
|
Sign up to set email alerts
|

Poly(1‐butene)/clay nanocomposites: Preparation and properties

Abstract: The preparation and properties of poly(1‐butene) (PB)/clay nanocomposites are described for the first time. Nanocomposites were prepared with the melt‐intercalation technique, using organically modified clay. The X‐ray diffraction patterns portrayed well‐defined diffraction peaks at higher d‐spacing than pristine clay, confirming the intercalation of polymer in silicate layers. Because PB exhibits time‐dependent polymorphism, the effect of clay on the phase transformation of PB was examined with thermal analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…The addition of nano-scale clays can change the crystallization kinetics, the crystalline morphology, the crystal forms, as well as crystallite size. [3][4][5][6][7][8][9][10][11][12][13] This difference in crystalline morphology, in turn, can significantly affect the overall mechanical and physical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nano-scale clays can change the crystallization kinetics, the crystalline morphology, the crystal forms, as well as crystallite size. [3][4][5][6][7][8][9][10][11][12][13] This difference in crystalline morphology, in turn, can significantly affect the overall mechanical and physical properties of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the cited work on PB-based nanocomposites, an interesting affinity of PB with clay emerged. Differently from what normally happens with polypropylene or polyethylene, a rather extensive reduction of clay tactoid size could be achieved in PB [4][5][6][7]. This feature and the compatibility of PB with polypropylene open a potential for PB as a highly performing vector to include clay within a polypropylene matrix.…”
mentioning
confidence: 95%
“…One of the aims was in fact to investigate if these different formulations could attain different composite morphologies and dispersions of the filler in the matrix, therefore studying its effect on the polymer semicrystalline framework and on the rate of phase transformation. The morphology of the composite was in fact shown to be key for the property improvement, for the stability of the metastable phase and also for the acceleration of the rate of the II!I transition [4][5][6][7]. WAXD was used to follow the phase transition, acquiring diffractograms at different times after cooling from the melt.…”
Section: Physical Mechanical Propertiesmentioning
confidence: 99%
“…The isothermal crystallization studies clearly indicated an enhancement in the crystallization rate, and resulted in a disturbed spherulitic morphology because of the dispersed clay layers [40,41] .…”
Section: Poly -1 -Butene (Pb)mentioning
confidence: 99%